Pemanfaatan Media Pembelajaran Berbasis Video Tutorial pada Mata Pelajaran Kewirausahaan di SMK Negeri 1 Bawolato - Femi Juwisda Lafau; Eka Septianti Laoli (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Learning media really supports the learning process for students, the results will have an impact on the level of student understanding in each subject. SMK Negeri 1 Bawolato is one of the schools whose students, especially class This research aims to utilize video tutorial-based learning media in entrepreneurship subjects. The aim is to increase student independence and interest in learning as evidenced by increased learning outcomes. Apart from that, this learning media is also expected to be useful for teachers and students in increasing knowledge related to the use of information technology. The type of research used is qualitative method research, where the results of the research show that there has been an increase in student learning outcomes. Initially students only passed at 75, now the average student completes at 80-95. Apart from that, the use of video tutorials also adds to the insight of teachers and students. The conclusion from this research is that teachers must continue to use learning media that suit students' interests, such as using video tutorials that utilize information technology.